Glycerophosphocholine and Glycerophosphoethanolamine Are Not the Main Sources of the In Vivo31P MRS Phosphodiester Signals from Healthy Fibroglandular Breast Tissue at 7 T - van der Kemp, Wybe J. M.; Stehouwer, Bertine L.; Runge, Jurgen H.; Wijnen, Jannie P.; Nederveen, Aart J.; Luijten, Peter R.; Klomp, Dennis W. J. (Frontiers in Oncology, 2016)
Purpose: The identification of the phosphodiester 31P MR signals in the healthy human breast at ultra-high field. Methods:In vivo 31P MRS measurements at 7 tesla of the phosphodiester signals in the breast were performed investigating the chemical shifts, the transverse- and the longitudinal relaxation times. Chemical shifts and transverse relaxation times were compared with non-ambiguous phosphodiester signals from the liver. Results: The chemical shifts of the phosphodiester signals are shifted -0.5 ppm with respect to glycerophosphocholine and -ethanolamine, and the transverse and longitudinal relaxation times for these signals are a factor 3 to 4 shorter than expected for aqueous glycerophosphocholine and -ethanolamine. Conclusions: The available experimental evidence suggests that glycerophosphocholine and –ethanolamine are not the main source of the phosphodiester signals measured in fibroglandular breast tissue at 7 tesla. These signals may predominantly originate from mobile phospholipids.